2010
DOI: 10.1038/eye.2010.47
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized comparison of DisCoVisc and Healon5 in phacoemulsification and intraocular lens implantation

Abstract: Purpose To compare two ophthalmic viscosurgical devices (OVDs), DisCoVisc (viscous dispersive) and Healon5 (viscoadaptive), in terms of their overall clinical performance during phacoemulsification and intraocular lens (IOL) implantation. Methods In 323 patients (DisCoVisc; 157, Healon5; 166), the surgeons evaluated on a three-point scale, the maintenance of anterior chamber (AC) during continuous curvilinear capsulorhexis (CCC), maintenance of AC during IOL implantation, retention during phacoemulsification,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 14 publications
0
22
0
3
Order By: Relevance
“…In this study, the mean ECD loss was approximately 80 cells/mm 2 (11.5%). Recent studies evaluating eyes with a normal preoperative ECD 7,20,28,29 report an endothelial cell loss of 1.8% to 15.0% after phacoemulsification. Previous studies 20,29 also found that the preoperative cell count was not predictive of corneal endothelial cell loss in eyes with a normal ECD.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, the mean ECD loss was approximately 80 cells/mm 2 (11.5%). Recent studies evaluating eyes with a normal preoperative ECD 7,20,28,29 report an endothelial cell loss of 1.8% to 15.0% after phacoemulsification. Previous studies 20,29 also found that the preoperative cell count was not predictive of corneal endothelial cell loss in eyes with a normal ECD.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] Bullous keratopathy is a vision-threatening complication, and pseudophakic bullous keratopathy is a leading indication for corneal graft surgery. 4 Although many procedures can reduce corneal endothelial damage, including the phaco-chop and soft-shell techniques, [5][6][7][8] there is often a reluctance to risk cataract surgery in cases in which the preoperative corneal endothelial cell density (ECD) is low, especially if it is below 1000 cells/mm 2 .…”
mentioning
confidence: 99%
“…Oshika et al [44] found significantly less mean ECL in patients who received viscous-dispersive OVDs (N ¼ 157 eyes, 1.8%) than in patients who received viscoadaptive OVDs (N ¼ 166 eyes, 3.8%) during phacoemulsification at 3 months after surgery. Another recent study with intraindividual comparisons of 78 eyes from 39 patients found significantly lower mean ECL with viscous-dispersive use (1.0%) than with very low viscosity dispersive use (3.5%) at 6 months after phacoemulsification [45].…”
Section: Ophthalmic Viscoelastic Devicesmentioning
confidence: 98%
“…14,0 (35,9%)/20,0 (51,3%) Grau (Provisc) 57 e outros dois comparando-o com hialuranato de sódio 2,3% (Healon5). 58,59 No presente estudo, a perda endotelial com o viscoelástico dispersivoviscoso mostrou ser estasticamente menor ao final do seguimento, parecendo haver uma melhor proteção endotelial com o uso do DisCoVisc em relação a HPMC. Não foi encontado diferença entre as duas soluções com relação a PIO e a ECC.…”
Section: (Tabela 1)unclassified
“…Porém, foram incluídos mais de um cirurgião, diferentes tipos de LIO e não foi informada a técnica utilizada para a fratura e conquista dos fragmentos nucleares. 58 Em estudo comparando SVE de baixo custo (hidroxipropilmetilcelulose 2,0% -Ocucoat) versus alto custo (hialurato de sódio 3,0%/ sulfato de condroitina 4,0% -Viscoat), não foi encontrado diferença estatística entre os grupos, sendo que o grupo da HPMC apresentou perda de 4,0 ± 12,6% ao final de 3 meses. Não foi informado a dureza dos núcleos operados.…”
Section: (Tabela 1)unclassified